1996
DOI: 10.1111/j.1365-2982.1996.tb00250.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology of porcine myenteric neurons revealed after vital staining of their cell bodies. A preliminary report

Abstract: Due to practical limitations in visualizing and getting access to the ganglionic components of large mammals, electrophysiology of the enteric nervous system has been restricted mainly to small laboratory animals, more particularly the guinea-pig. The use of the vital dye 4-(4-diethylaminostyry1)-N-methylphyridinium iodide (4-Di-2-ASP), however, overcomes some of these difficulties. A 20-min incubation period with this dye, followed by a minimum period of 4 h in Krebs solution, suffices to stain the neuronal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…A previous study had shown that 4-Di-2-ASP did not affect the viability of cells in different kinds of tissue in several species [12]. A recent paper demonstrated that the normal electrophysiological activity of porcine myenteric neurons was not altered by long-term incubation with 4-Di-2-ASP [14]. In the present study, the electrical properties of guinea pig gallbladder neurons were similarly not affected by 4-Di-2-ASP.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…A previous study had shown that 4-Di-2-ASP did not affect the viability of cells in different kinds of tissue in several species [12]. A recent paper demonstrated that the normal electrophysiological activity of porcine myenteric neurons was not altered by long-term incubation with 4-Di-2-ASP [14]. In the present study, the electrical properties of guinea pig gallbladder neurons were similarly not affected by 4-Di-2-ASP.…”
Section: Discussionsupporting
confidence: 61%
“…This is due to the diffuse nature of the ganglia in the human gallbladder, as the ganglia are not found in a discrete layer, but are found at any level within the smooth muscle. In comparison, as the porcine myenteric plexus is in a discrete layer, once the ganglia could be identified electrophysiology was possible with a rate of success equivalent to that in the guinea pig [14]. Another study involving electrical recordings from neurons of the human gut tube did not utilize any vital dyes [15].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it should be stressed that, despite a large degree of similarity between the neurochemically and morphologically identified neuron populations of the OSP and MP, both nerve networks are not identical, as illustrated by the absence of the Dogiel type I cell type in the OSP and the different proportions of particular neuron classes in both networks. In addition, the difference in proportion of neurons with the electrophysiological AH phenotype between the OSP (70%) and the MP (3-17%) (Cornelissen et al, 1996(Cornelissen et al, , 1999(Cornelissen et al, , 2000Thomsen et al, 1997a,b) is not in support of a hypothesis that the OSP has to be regarded as just a topographical subdivision of the MP.…”
Section: Vasomotor Neuronsmentioning
confidence: 65%
“…Electrophysiological Kunze et al, 1997Kunze et al, , 1998Furness et al, 1998), tracing (Song et al, 1991;Kirchgessner et al, 1996), and c-fos (Kirchgessner et al, 1992) experiments have led to the assumption that the cell bodies of intrinsic mucosal mechanosensitive neurons are located in the submucosa, whereas the myenteric plexus (MP) harbours chemo-and stretch-sensitive neurons (Furness et al, 1999). Though differing in neurochemical content (Timmermans et al, 1990(Timmermans et al, , 1992b(Timmermans et al, , 1997 and electrophysiological properties (Brookes et al, 1987;Cornelissen et al, 1996Cornelissen et al, , 1999, some neurons in both the submucous and the myenteric plexuses of pig and human intestine were found to exhibit a similar type II morphology (Scheuermann et al, 1987a;Timmermans et al, 1992a).…”
Section: Intrinsic Primary Afferent Neurons Of the Ospmentioning
confidence: 99%
“…Pigs are one of the few common and readily available mammals that are omnivorous. Both with regard to the anatomic organisation of the intrinsic nerve networks and to the morphologic and electrophysiological features of distinct subclasses of enteric neurons, the pig model seems to resemble more closely the human situation than the guinea pig model does [15][16][17][18]. The aim of our study was to establish the age-related development of the mucosal innervation in porcine small and large bowel from foetal to adult life.…”
Section: Introductionmentioning
confidence: 99%